Indonesian public hospitals’ online reputation: Mapping identity and communication dimensions - Kussusanti, Kussusanti; Arindita, Ruvira; Hasna, Safira (Universitas Padjadjaran, 2025)
Background: Background: Effective communication is instrumental in reputation building, shaping public perception of an organization. The principle extends to hospitals, which are increasingly benefiting from online media. The concept of online reputation is related to the perception of hospital credibility and image cultivated through digital platforms. This includes key components such as public trust, patient engagement, and institutional transparency. However, an important gap in the existing literature is the absence of a comprehensive analysis systematically mapping reputation of public hospitals across Indonesia. Purpose: This research aims to map reputation of public hospitals in Indonesia as reflected in online media. The necessity was evident in the sustained negative public perception of several hospitals. Method: This research was conducted quantitatively through content analysis with a sample of 100 public hospitals. The unit of analysis was online media content, namely website, Instagram, Facebook, and YouTube of Central Public Hospitals (Rumah Sakit Umum Pusat/RSUP) and Regional Public Hospitals (Rumah Sakit Umum Daerah/RSUD) from July 1-31, 2024. The two dimensions measured were corporate identity and communication activities. In-depth interviews were also conducted. Results: This research reported reputation map for RSUP and RSUD in Indonesia. The results showed that A-class hospitals consistently fell in the top quartile (Q1). However, reputation map suggested a more even distribution across Q1 to Q4 for B and C-class hospitals. Only one B-class and C-class hospitals were in Q4 and Q1 or Q2, respectively. Conclusion: Indonesian public hospitals used Instagram for interactivity and website for formal information to enhance reputation through corporate identity and communication. Implications: This research contributes to the development of reputation theory, particularly in hospital industry, and suggests that hospitals build a strong reputation through online media.